Life-cycle of Rhyacionia buoliana (Lepidoptera: Tortricidae) and degree-day accumulations in Chile - HUERTA-F., AMANDA; JORQUERA-M., PATRICIO (Revista Colombiana de Entomología, 2009)
The European pine shoot moth, Rhyacionia buoliana (Lepidoptera: Tortricidae), is the most important pest affecting plantations of Pinus radiata in Chile. Even when it does not cause tree death, the commercial value is reduced. In order to study the life cycle of this insect, attacked shoots were sampled every 10 days from September 2000 to May 2002, in P. radiata stands located in the commune Paredones, Region of Libertador Bernardo O’Higgins, Chile. The flight of male R. buoliana was monitored at the same time through pheromone traps. Degree-day (DD) accumulations were computed using the rectangle method, with a minimum temperature threshold of -2.2°C. Every stage of the life cycle was associated with DD accumulations. R. buoliana life cycle was univoltine. Approximately 5,780 DD were required to complete one generation. For pest control purposes, the 50 and 80% flight of adult males, based on capture of the first adult in pheromone traps, were reached at 877 and 1,207 DD, respectively. Information on the life cycle, periods of caterpillar activity, and DD accumulations presented in this study can be used in management programs to improve the efficiency of monitoring and controlling populations of this pest.